PENGARUH IKLAN VIDEO YANG MENGGUNAKAN INFLUENCER SEBAGAI MODEL DI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN UNTUK PRODUK PERAWATAN TUBUH - Vanessa Gloria; Nurrani Kusumawati (PT Naureen Digital Education, 2023)
The presence of video advertising can be an effective strategy for providing new sensory experiences to users and driving purchasing decisions for body care products. However, there are still video ads on social media platforms (Instagram, YouTube, and TikTok) are less effective in influencing customers or their audiences to make purchasing decisions, notably in the beauty and body care industries. As a result, the purpose of this study is to examine the impact of expected factors altered by video advertising that leverages influencers as models on social media on customers' purchasing decisions for body care goods. This study combines qualitative and quantitative analysis, open coding approaches are used to examine qualitative data, and Partial Least Squares Structural Equation Modeling (PLS-SEM) is used to study quantitative data. The study's findings suggest that video advertising has a positive influence on customers' purchasing decisions for body care items. Furthermore, empathy, preferred social media, and purchase intention all have a significant and positive impact on customers' purchasing decisions. These findings are likely to provide insights into ways for exploiting and optimizing the potential of video advertising that uses influencers as models in influencing customers' purchasing decisions for social media-available body care items